2019
DOI: 10.1002/ejic.201900946
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Milling Induced Structure Changes in Phenylphosphonic Acid Functionalized LiMn2O4 Nanocrystals – Synthesis, Rietveld Refinement, and Thermal Stability

Abstract: Spinel LiMn 2 O 4 formed in a solid-state reaction was treated with a high energy planetary ball mill. A mechanochemical in situ surface functionalization of the nanocrystallites with a size smaller than 10 nm was achieved by addition of phenylphosphonic acid. The functionalization was proven by infrared spectroscopy and it can be shown that it prevents the formation of Mn 2 O 3 during the milling process. Structural changes of the samples were investigated via XRD and Rietveld refinement. Mild milling conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…LiFePO 4 has great potential as a cathode material for high-performance lithium-ion batteries. At the same time, it has been found that the ground nanomaterials such as lithium iron phosphate (LiFePO 4 ), lanthanum ferrite (LaFeO 3 ), 186 lithium cobalt oxide (LiCoO 2 ), 187,188 and lithium manganate (LiMn 2 O 4 ) [189][190][191][192] have better electrochemical performance. These materials could also provide higher energy density, longer cycle life, and better rate capability for the next generation of lithium-ion batteries.…”
Section: Life 5 O 8 Ceramic Powdermentioning
confidence: 99%
“…LiFePO 4 has great potential as a cathode material for high-performance lithium-ion batteries. At the same time, it has been found that the ground nanomaterials such as lithium iron phosphate (LiFePO 4 ), lanthanum ferrite (LaFeO 3 ), 186 lithium cobalt oxide (LiCoO 2 ), 187,188 and lithium manganate (LiMn 2 O 4 ) [189][190][191][192] have better electrochemical performance. These materials could also provide higher energy density, longer cycle life, and better rate capability for the next generation of lithium-ion batteries.…”
Section: Life 5 O 8 Ceramic Powdermentioning
confidence: 99%